Pengaruh Penyiraman Rutin Terhadap Pertumbuhan Bibit Tanaman Nangka (Artocarpus heterophyllus) di UPTD BSPTH Dinas Kehutanan Provinsi Sumatera Barat - Syarifatus Salni; Filza Yulina Ade; Mika Lestaria (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Jackfruit (Artocarpus heterophyllus) is a multipurpose plant with high ecological and economic value developed at the Regional Technical Implementation Unit for Forest Plant Seed Certification Center, West Sumatera Provincial Forestry Service. The success of jackfruit seedling cultivation is greatly determined by proper maintenance techniques, particularly regular watering. The aim was to observe and describe the effect of regular watering on jackfruit seedling growth. A qualitative descriptive method with direct field observation was employed. Results showed that seedlings watered regularly twice daily (morning and evening) demonstrated optimal growth, including gradual and consistent height increase, fresh green leaves, and sturdy stems. Conversely, seedlings with suboptimal watering exhibited wilting, slow growth, and yellowing of leaves. Seedling growth was also supported by a mixed growing medium of soil, rice husk charcoal, compost, and cocopeat effectively maintained moisture and aeration. Regular watering is proven to be the primary determinant of successful jackfruit seedling production at the UPTD BSPTH nursery.